Textual and contextual voices of translation - Alvstad, Cecilia; Greenall, Annjo Klungervik; Jansen, Hanne; Taivalkoski-Shilov, Kristiina (Benjamins translation library, 2017)
The notion of voice has been used in a number of ways within Translation Studies. Against the backdrop of these different uses, this book looks at the voices of translators, authors, publishers, editors and readers both in the translations themselves and in the texts that surround these translations. The various authors go on a hunt for translational agents' voice imprints in a variety of textual and contextual material, such as literary and non-literary translations, book reviews, newspaper articles, academic texts and e-mails. While all stick to the principle of studying text and context together, the different contributions also demonstrate how specific textual and contextual circumstances require adapted methodological solutions, ending up in a collection that takes steps in a joint direction but that is at the same time complex and pluralistic. The book is intended for scholars and students of Translation Studies, Comparative Literature, and other disciplines within Language and Literature.